2016
DOI: 10.4137/cmc.s39708
|View full text |Cite
|
Sign up to set email alerts
|

Computational Representations of Myocardial Infarct Scars and Implications for Arrhythmogenesis

Abstract: Image-based computational modeling is becoming an increasingly used clinical tool to provide insight into the mechanisms of reentrant arrhythmias. In the context of ischemic heart disease, faithful representation of the electrophysiological properties of the infarct region within models is essential, due to the scars known for arrhythmic properties. Here, we review the different computational representations of the infarcted region, summarizing the experimental measurements upon which they are based. We then f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…However, the induced PVC could still propagate further toward the distal end, where the tissue had recovered excitability, and reenter back around the scar [24]. In this work we have shown that conduction block can occur as a result of sourcesink mismatch rather than heterogeneities in AP duration or in the ERP.…”
Section: Unidirectional Conduction Blockmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the induced PVC could still propagate further toward the distal end, where the tissue had recovered excitability, and reenter back around the scar [24]. In this work we have shown that conduction block can occur as a result of sourcesink mismatch rather than heterogeneities in AP duration or in the ERP.…”
Section: Unidirectional Conduction Blockmentioning
confidence: 79%
“…Recently, Connolly et al [24] have demonstrated that a premature stimulus capturing inside the isthmus may be blocked from propagating to the myocardium as the effective refractory period (ERP) was shown to be higher at the isthmus' proximal mouth. However, the induced PVC could still propagate further toward the distal end, where the tissue had recovered excitability, and reenter back around the scar [24].…”
Section: Unidirectional Conduction Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, a shorter APD will also shorten the wavelength, making the formation of a sustained re-entrant circuit more likely. On the other hand, a longer APD at the BZ may be arrhythmogenic in the presence of an isthmus (Connolly and Bishop, 2016 ), where propagation is initially blocked, due to increased refractoriness, but might enter the isthmus creating a re-entrant circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Connolly and Bishop 16 provide a detailed and nuanced overview of the many different computational strategies used to represent infarcted myocardium in simulations of cardiac electrophysiology. Given the recent surge of interest in the use of simulations conducted in patient-specific models reconstructed from clinical imaging data to derive useful insights for arrhythmia treatment, such as custom-tailored ablation planning, this is a timely and highly relevant review.…”
mentioning
confidence: 99%